2022
DOI: 10.1021/acsaem.2c00533
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Li Batteries with NCM–Garnet-Based Composite Cathodes: The Impact of NCM Composition on Material Compatibility

Abstract: Garnet-based all-solid-state batteries (ASBs) with high energy density require composite cathodes with high areal loading and high-capacity cathode active materials. While all ceramic cathodes can typically be manufactured via cosintering, the elevated temperatures necessary for this process pose challenges with respect to material compatibility. High-capacity cathode active materials like Ni-rich LiNi x Co y Mn1–x–y O2 (NCM) show insufficient material compatibility toward the solid electrolyte Li6.45Al0.05La3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Because ASSBs comprise all-solid-state components, including solid electrolytes, intimate contacts between the active materials and at the electrolyte/electrode interface are essential for the stable operation of ASSBs. Similar to LIBs, CAMs in ASSBs degrades owing to irreversible phase transition, microcrack formation, and TM migration. , However, unlike LIBs, where the liquid electrolyte penetrates into microcracks and develops an excessive CEI layer, the strain and microcracks of CAMs in ASSBs cause contact loss within the CAM and in the electrolyte/CAM interface. These contact losses impede Li-ion transport and increase interfacial resistance, which is the most significant issue in ASSBs.…”
Section: Challenges Induced By Strain In Cathode Materialsmentioning
confidence: 99%
“…Because ASSBs comprise all-solid-state components, including solid electrolytes, intimate contacts between the active materials and at the electrolyte/electrode interface are essential for the stable operation of ASSBs. Similar to LIBs, CAMs in ASSBs degrades owing to irreversible phase transition, microcrack formation, and TM migration. , However, unlike LIBs, where the liquid electrolyte penetrates into microcracks and develops an excessive CEI layer, the strain and microcracks of CAMs in ASSBs cause contact loss within the CAM and in the electrolyte/CAM interface. These contact losses impede Li-ion transport and increase interfacial resistance, which is the most significant issue in ASSBs.…”
Section: Challenges Induced By Strain In Cathode Materialsmentioning
confidence: 99%
“…Roitzheim et al have performed a detailed study on secondary phase formation during the co-sintering of NCM111/NCM811 and LLZO : Ta electrolytes with and without B-doping. 222 It was found that the interchange between Zr and Mn is more favorable compared to the interchange with Ni and Co as well as La ↔ Ni and La ↔ Co. It leads to the formation of a La-based, Mn-rich secondary phase of LaCo 1−3 , which is predominant in NCM111.…”
Section: Ni-rich Ncms For Solid-state Libsmentioning
confidence: 99%
“…More recently, anode-free lithium metal batteries (AFBs), obtained by removing the metallic lithium anode at the initial state, have shown a potential to further increase battery energy density. The low CE and poor cycling reversibility reported in the literature for these systems, however, are not satisfactory compared to those of LMBs, mainly because there is no lithium reservoir to replenish lost lithium. Similar to LMBs, AFBs also suffer from problems originating from the creation of high surface area lithium and the formation of inactive lithium, which is directly correlated with low CE. Over the past few decades, extensive efforts have been devoted to understanding the mechanism of the formation of high surface area lithium deposition and developing strategies to achieve high CE in LMBs and AFBs, such as developing new electrolyte/additives, electrochemical treatments, surface engineering, solid-state electrolytes, and lithium host modification , and so on. , …”
Section: Introductionmentioning
confidence: 99%